PREDIKSI PENGGUNAAN TAWAS DAN PH PADA PROSES PENGOLAHAN AIR SUNGAI BENGAWAN SOLO - Ronggur Hamonangan Panjaitan, Jabosar ((JITEK)Jurnal Ilmiah Teknosains, 2025)
Bengawan Solo River is the longest river in Java that can be used as a water source. Pollution of the Bengawan Solo River causes high BOD values so that it does not meet the standards. In this study, the prediction of alum used and pH values in the Bengawan Solo River water treatment was studied. The results of this study indicated that the BOD parameter has a large influence on the use of alum compared to discharge and residence time. High BOD values increase the need for alum. The highest alum requirement was obtained from Bengawan Solo River water treatment with a discharge of 6.4 x 106 m3/hour, 19.8 ppm BOD, and 12 hours residence time. While the lowest alum requirement was obtained from Bengawan Solo River water treatment with a discharge of 5.2 x 106 m3/hour, 2 ppm BOD, and 3 hours residence time. The use of alum in the Bengawan Solo River water treatment does not show a significant effect on the resulting pH value, which ranges from 10 to 11.